Volatility and Transmission of Coffee Prices in Indonesia - Sukiyono, Ketut; Dita, Putri Tiara; Romdhon, Muhammad Mustopa (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2025)
Commodity prices, including prices for agricultural products, play a very important function in making decisions both in production and marketing. Therefore, the study of price volatility and transmission is very important to be carried out to obtain price behavior in the market, including coffee prices. This research is aimed at analyzing the volatility and transmission of Indonesian coffee prices at the producer, the national (f.o.b price), and the International level. The data used are monthly data of coffee beans at producer level in Bengkulu province, Indonesia f.o.b prices, and International coffee prices in 2010:1